2014
DOI: 10.4103/0253-7613.132182
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indica attenuates cisplatin-induced neurotoxicity in rats

Abstract: Objective:The objective of this study is to investigate the neuroprotective effects of Azadirachta indica leaves against cisplatin (CP)-induced neurotoxicity.Materials and Methods:Female Wistar rats were treated with vehicle (control); a single intraperitoneal 5 mg/kg CP (CP group); neem leaves (orally 500 mg/kg) for 5 and 10 days, N5 and N10 groups, respectively; neem leaves (500 mg/kg) for 5 days after CP injection, collagenous protein nitrogen (CPN) group; neem leaves (500 mg/kg) for 5 days before CP inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The NO radicals play a crucial role in inducing inflammatory response, and their toxicity propagated only when they react with O 2 •− radicals to form peroxynitrite, which damages biomolecules such as proteins, lipids, and nucleic acids [ 43 ]. In the present study, we showed that pomegranate juice restrained NO generation, thus suggesting its applicability as a potent and novel therapeutic agent for scavenging NO.…”
Section: Discussionmentioning
confidence: 99%
“…The NO radicals play a crucial role in inducing inflammatory response, and their toxicity propagated only when they react with O 2 •− radicals to form peroxynitrite, which damages biomolecules such as proteins, lipids, and nucleic acids [ 43 ]. In the present study, we showed that pomegranate juice restrained NO generation, thus suggesting its applicability as a potent and novel therapeutic agent for scavenging NO.…”
Section: Discussionmentioning
confidence: 99%
“…It is an alkylating agent which at effective higher doses causes many adverse effects such as neurotoxicity, nephrotoxicity, and genotoxicity [12, 30]. CP-induced nephrotoxicity can result in severe renal tubular injury leading to acute renal failure [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study was performed to investigate the neuroprotective effects of Azadirachta indica leaves against cisplatin- (CP-) induced neurotoxicity and results showed that morphological findings of neem before and after CP injection implied a well-preserved brain tissue. No changes, in biochemical parameters, were observed with neem treated groups [ 97 ].…”
Section: Neuroprotective Effectsmentioning
confidence: 99%